IMPLEMENTATION OF THE MINIMUM INVESTMENT RETURN SYSTEM ON THE PROFIT SHARING OF MUDARABAH FINANCING: A CONTEMPORARY MUAMALAH FIQH PERSPECTIVE - Musfiroh, Mila Fursiana Salma; Miftakhussurur, Mohammad Qoid; Kaukab, M. Elfan; Sabrina, Laila; Hartiyah, Sri; Nugroho, Ahmad Fahmi (Jurnal 'Ulwan, 2024)
Mudarabah financing is one of the products of sharia banking which has been approved by Fatwa of DSN MUI No: 07-DSN-IV/2000 which discusses mudarabah financing and its provisions. This research aims to determine the implementation of minimum investment returns for Mudarabah financing profits at KSPPS Tamzis Bina Utama Branch Office of Batur Banjarnegara and contemporary muamalah fiqh perspectives on the implementation of minimum investment returns for mudarabah financing profits. The field research study is descriptive qualitative in nature with the research object being revenue sharing from mudarabah financing based on minimum investment returns at KSPPS Tamzis Bina Utama. Data collection by interviews and documentation. The data was then tested for data validity using theoretical triangulation and qualitative descriptive analysis. The research results show that the profit sharing of mudarabah financing at KSPPS Tamzis Bina Utama is in accordance with the theory of profit sharing of mudarabah financing because there are no elements of gharar, maisir, compulsion and disadvantage from either party. This financing is in the nature of a loan so that when members do not make a profit, they are only obliged to repay the loan at the beginning of the contract without any additional profit sharing. Meanwhile, the determination of profit-sharing provisions at the beginning of the contract is permitted by Imam Syafi'i based on sales or money that has been generated from mudarabah financing and KSPPS Tamzis Bina Utama uses a minimum investment return system to determine the profit sharing. This system which is run by KSPPS Tamzis Bina Utama is a form of ijtihad which is used as a reference for the profits that will be obtained, not as a certainty in the profits that will be obtained, and still be negotiated if the mudarib has not met the profits determined by the investment return requirements minimum. So, it can be concluded that the system of minimum investment returns on mudarabah financing loans applied at KSPPS Tamzis Bina Utama according to contemporary muamalah fiqh is legally valid because of the principle of mutual consent, permissibility, and the absence of gharar elements that are uncertain in the transaction.